Evaluation of Short-Term Use of Positive and Oscillating Positive Expiratory Pressure in Bronchial Drainage in Cystic Fibrosis Patients During an Exacerbation of The Disease - Jarosław Prusak; Katarzyna Warzeszak; Piotr Kurzeja (Rehabilitacja Medyczna)
Introduction: Cystic fibrosis is the most common severe autosomal recessive genetic disease in Caucasians. The main disorder in the course of cystic fibrosis is the accumulation of a large amount of thick and viscous secretion in the bronchi.Objectives: To assess the efficacy of the usage of selected devices generating positive expiratory pressure (PEP S System device) and oscillating positive expiratory pressure (OPEP Aerobika, Flutter devices) in bronchial drainage in cystic fibrosis patients during exacerbation of the disease.Methods: The study involved 35 cystic fibrosis patients with an average age of 23.38.5 yrs. In the study group, a 4-day bronchial drainage cycle was used.Results: The FEV1 indicator for the whole group was 55.623% of the predicted value, and the size of the improvement, similarly to FVC and MEF25, was statistically significant (p<0.001). The mean value of the expectorated secretion in the bronchial drainage program was 88.175.3 ml in the OPEP Aerobika group, 80.589 ml in the OPEP Flutter group and 63.8105 ml in the PEP group. There were no differences between groups also in the value of collected secretion and in improvement of the lung function.Conclusions: The results of the study indicate the approximate effectiveness of the devices and methods of bronchial drainage used in patients with cystic fibrosis in exacerbation of the disease.